2023
DOI: 10.3390/ijms241612575
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Design through Grafting of Diazonium Salts—A Critical Review on Catalyst Stability

Szymon Smołka,
Katarzyna Krukiewicz

Abstract: In the pursuit of designing a reusable catalyst with enhanced catalytic activity, recent studies indicate that electrochemical grafting of diazonium salts is an efficient method of forming heterogeneous catalysts. The aim of this review is to assess the industrial applicability of diazonium-based catalysts with particular emphasis on their mechanical, chemical, and thermal stability. To this end, different approaches to catalyst production via diazonium salt chemistry have been compared, including the immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Most devised methodologies for grafting organic layers or AuNPs on copper metal have employed electrochemical processes for decades. The electrochemical reduction of aryldiazonium salts on a copper surface to form strongly bonded organic layers has been employed to inhibit corrosion and develop ice-phobic surfaces . Mooste et al reported the electrochemical grafting of anthraquinone diazonium salts on copper electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…Most devised methodologies for grafting organic layers or AuNPs on copper metal have employed electrochemical processes for decades. The electrochemical reduction of aryldiazonium salts on a copper surface to form strongly bonded organic layers has been employed to inhibit corrosion and develop ice-phobic surfaces . Mooste et al reported the electrochemical grafting of anthraquinone diazonium salts on copper electrodes .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has predominantly focused on modulating catalyst properties and investigating the impact of catalyst size, shape, and chemical composition [ 18 , 19 ]. Recently, chemically modified catalysts with thin organic layers were proposed as a promising approach to modulating electrocatalytic activity [ 20 ]. However, this approach is at an early stage and more research efforts are needed.…”
Section: Introductionmentioning
confidence: 99%